Designing Vegan Leather Based Coffee Grounds Merchandise as an Effort to Optimize Green Brand Awareness in Work Unusual - Putri Aulia Yahya; Arini Arumsari; Muchlis Muchlis (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The growth of coffee shops in the city of Bandung encourages brand competition that not only focuses on product quality but also on the ability to convey sustainability values to consumers. Work Unusual is a coffee shop that has implemented environmentally friendly practices, but the level of consumer green brand awareness is still relatively low due to the limitations of the communication media used. This research aims to design sustainable merchandise as a physical communication medium to optimize green brand awareness at Work Unusual. The method used is design thinking with the stages of empathize, define, ideate, prototype, and testing. The design focuses on the development of merchandise in the form of laptop sleeves made of vegan leather based on coffee grounds with the application of interlocking and quilting techniques. The results of the research are in the form of a laptop sleeve prototype that has functional, aesthetic, and sustainability values, and is considered capable of nonverbally representing Work Unusual’s environmental commitment. The conclusion of the study shows that sustainable merchandise design has the potential to be an effective visual communication strategy in supporting the optimization of green brand awareness in sustainability-based coffee shops.